RAPESEED AS THE SOURCE OF PROTEINS: A REVIEW - Tomić, Damjana; Simeunović, Jovana; Đermanović, Branislava; Maric, Aleksandar; Sakač, Marijana; Šarić, Bojana; Jovanov, Pavle (Food and Feed Research, 2025)
Rapeseed proteins can be isolated as high-value components from residual materials of oilseed processing. This review provides an overview of rapeseed protein isolate production, with an emphasis on conventional alkaline extraction and alternative methods. Special attention is given to antinutrient compounds found in rapeseed (glucosinolates, phenolic compounds, phytic acid, and others) and the strategies to mitigate them. Techniques that are effective in not only removing antinutrients but also increasing protein yield and reducing extraction time are discussed, including ultrasound, microwave, and enzymatic pretreatments. Enzymatic hydrolysis for obtaining rapeseed protein hydrolysates is also discussed, along with novel extraction methods for protein isolate production, particularly the use of natural deep eutectic solvents (NADES).